Exploration of the truncated cytosolic Hsp70 in plants - unveiling the diverse T1 lineage and the conserved T2 lineage - Chen, Yi-Jing; Cheng, Sou-Yu; Liu, Cheng-Han; Tsai, Wen-Chieh; Wu, Hsin-Hsin; Huang, Ming-Der (Frontiers in Plant Science, 2023)
The 70-kDa heat shock proteins (Hsp70s) are chaperone proteins involved in protein folding processes. Truncated Hsp70 (Hsp70T) refers to the variant lacking a conserved C-terminal motif, which is crucial for co-chaperone interactions or protein retention. Despite their significance, the characteristics of Hsp70Ts in plants remain largely unexplored. In this study, we performed a comprehensive genome-wide analysis of 192 sequenced plant and green algae genomes to investigate the distribution and features of Hsp70Ts. Our findings unveil the widespread occurrence of Hsp70Ts across all four Hsp70 forms, including cytosolic, endoplasmic reticulum, mitochondrial, and chloroplast Hsp70s, with cytosolic Hsp70T being the most prevalent and abundant subtype. Cytosolic Hsp70T is characterized by two distinct lineages, referred to as T1 and T2. Among the investigated plant and green algae species, T1 genes were identified in approximately 60% of cases, showcasing a variable gene count ranging from one to several dozens. In contrast, T2 genes were prevalent across the majority of plant genomes, usually occurring in fewer than five gene copies per species. Sequence analysis highlights that the putative T1 proteins exhibit higher similarity to full-length cytosolic Hsp70s in comparison to T2 proteins. Intriguingly, the T2 lineage demonstrates a higher level of conservation within their protein sequences, whereas the T1 lineage presents a diverse range in the C-terminal and SBDα region, leading to categorization into four distinct subtypes. Furthermore, we have observed that T1-rich species characterized by the possession of 15 or more T1 genes exhibit an expansion of T1 genes into tandem gene clusters. The T1 gene clusters identified within the Laurales order display synteny with clusters found in a species of the Chloranthales order and another species within basal angiosperms, suggesting a conserved evolutionary relationship of T1 gene clusters among these plants. Additionally, T2 genes demonstrate distinct expression patterns in seeds and under heat stress, implying their potential roles in seed development and stress response.